A billion bootstraps : - Smith, Philip B. (McGraw-Hill, 2007)
Billion Bootstraps explains how ordinary people can accelerate the microcredit movement by investing charitable donations in specific programs and then leveraging those contributions so the net cost to lift one person out of poverty is remarkably low. You'll discover how to get more for your money by donating with the mind-set of an investor and calculating measurable returns-returns that will change lives and societies forever